A Survey-Based Study of Medication Safety Competence and Its Relationship with Safe Nursing Care among Nurses - Maryam Aghabarary; Fariba Katebi; Mostafa Bijani (SAGE Open Nursing)
Introduction Medication safety competence is a critical factor in enhancing patient safety. Safe nursing care is also a fundamental component of nursing service quality and a key indicator in clinical governance and risk management programs. Objective This survey-based study, conducted for the first time in Iran, aimed to determine medication safety competence and its relationship with safe nursing care among nurses. Methods This cross-sectional study used questionnaires to collect data . The study population consisted of all nurses working in clinical departments across eight hospitals in North Khorasan Province, northeastern Iran. The total number of nurses in these eight hospitals was 1,025. Given the number of hospitals and the proportion of nurses in each, a proportional sampling method was first employed, followed by convenience sampling within each hospital based on inclusion criteria. The data collection tools included the electronic version of the Medication Safety Competence Scale, Assessment of Safe Nursing Care Questionnaire, and a demographic characteristics section. One-sample t-test was used to compare the mean of the samples with the mean score criterion. The Pearson correlation test was used to assess the relationship between medication safety competence and safe nursing care. To predict safe nursing care based on medication safety competency, multiple linear regression analysis was performed using the simultaneously (Enter) method. To analyze medication safety competence and safe nursing care based on participants’ demographic characteristics, independent t-tests and analysis of variance (ANOVA) were conducted. Data analysis was performed using SPSS software version 28, with a significance level set at p  ≤ .05. Results Out of the 500 nurses who received the questionnaire link, 429 completed the questionnaire. The mean medication safety competence of the participants was 148.85 ± 19.21, indicating a moderate level. The mean safe nursing care score was 314.71 ± 36.82, indicating a desirable level. A significant direct relationship was observed between medication safety competence and safe nursing care. The role of medication safety competence and department type in predicting safe nursing care was confirmed. Working in the emergency department was negatively associated with safe nursing care compared to other departments. Conclusion The participants’ medication safety competence was at a moderate level, while their safe nursing care was at a desirable level. It is recommended that nursing managers develop plans to enhance medication safety competence, with a particular emphasis on the components of safe nursing care.